Disequilibrium, Buffer Stocks and Consumers' Expenditure on Non-Durables - Cuthbertson, Keith; Barlow, David (The Review of Economics and Statistics, 1991)
The authors examine the importance of a disequilibrium real balance effect on non-durable consumers' expenditure in the U.K. Using cointegration techniques and the Johansen procedure they first establish a desired long-run demand function for liquid assets depending on income, wealth and a set of interest rates. Deviations of liquidity from this desired level cause changes in consumption via intertemporal substitution but via its effect on disequilibrium liquidity. Consumption is modeled in an error-correction framework and is also found to depend on income and financial wealth. Both the disequilibrium liquidity and wealth terms may be picking up the effects of financial liberalization (e.g. "mortgage leak") on consumption as funds released will be temporarily held in financial assets. They also find some evidence that changes in the distribution of income have an independent effect on aggregate consumption. Copyright 1991 by MIT Press.